1998
DOI: 10.1103/physrevlett.80.4245
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Photoemission Spectral Function of Cuprates: Insulators and Hole- and Electron-Doped Superconductors

Abstract: Angle-resolved photoemission studies on Sr 2 CuO 2 Cl 2 at a temperature below its Néel temperature reveal detailed momentum dependent line shape changes as a function of wave vector. While a sharp quasiparticlelike peak is observed near (p͞2, p͞2), broad peaks are observed near (p, 0). Additional second and third neighbor hopping terms must be added to the t-J Hamiltonian to account for both the dispersion and the line shape. It is found that this Hamiltonian can be used to explain the measured momentum depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
292
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(340 citation statements)
references
References 26 publications
42
292
6
Order By: Relevance
“…Along ⌫ to ( ,0) there is a broad peak at ϳ1.1-1.2 eV binding energy, which can only be observed in a range of k vectors from ϳ50% to ϳ85% of the distance between ⌫ and ( ,0) and has its maximum spectral intensity at ϳ70% of the distance between ⌫ and ( ,0). These results are in agreement with all previous studies of the first electron-removal states of Sr 2 CuO 2 Cl 2 , 11,13 and the closely related Ca 2 CuO 2 Cl 2 , 14,15 which were recorded at about the same photon energy ͑22-25 eV͒ as the spectra shown in Fig. 1.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Along ⌫ to ( ,0) there is a broad peak at ϳ1.1-1.2 eV binding energy, which can only be observed in a range of k vectors from ϳ50% to ϳ85% of the distance between ⌫ and ( ,0) and has its maximum spectral intensity at ϳ70% of the distance between ⌫ and ( ,0). These results are in agreement with all previous studies of the first electron-removal states of Sr 2 CuO 2 Cl 2 , 11,13 and the closely related Ca 2 CuO 2 Cl 2 , 14,15 which were recorded at about the same photon energy ͑22-25 eV͒ as the spectra shown in Fig. 1.…”
supporting
confidence: 82%
“…10 Therefore photoemission, as a fast and local probe, still registers the effect of antiferromagnetic order even 50 K above the Néel temperature. 11 The dynamics of a hole in a two-dimensional antiferromagnetic background is of fundamental interest itself and there have been numerous theoretical 12 and experimental 11,[13][14][15][16] studies of this subject. Of primary interest here are the lowest-lying states in an ARPES spectrum, the so-called first electron-removal states, which, according to most theoretical results, should be comprised of a lowbinding-energy quasiparticle peak ascribed to the so-called Zhang-Rice singlet 17 ͑ZRS͒ followed by incoherent spectral weight at higher binding energy due to quasiparticle dressing.…”
mentioning
confidence: 99%
“…Although some controversial results have been obtained, various studies including exact diagonalization [2,3], series expansion [4], and Monte Carlo simulations [5,6] enable us to understand the hole-dynamics quantitatively, at least to some extent. In particular, these studies all obtained minima of the single-hole dispersion relation at lattice momenta (± π 2a , ± π 2a ) in the Brillouin zone of the square lattice which is in agreement with experimental results [7,8,9].…”
Section: Introductionsupporting
confidence: 77%
“…The third-neighbor interaction t nN N N ≃ -40 meV could tentatively be omitted. Recent analysis of angle-resolved photoemission spectroscopy data has shown that both t N N N and t nN N N are necessary for understanding the dispersion and line shape of the spectral function in the t-J model [26]. Tohyama et al [25] have estimated the ratio t N N N /t N N and t nN N N /t N N to be -0.12 and 0.08, respectively, by fitting the tight-binding Fermi surface to the experimental one in the overdoped sample [47] on the assumption that in the overdoped region the Fermi surface of the tight-binding band is the same as that of the t-t'-t"-J model.…”
Section: Discussionmentioning
confidence: 99%
“…The hole-hole repulsion V ij is likely to play a role, influencing the mean distance between the holes. Different extensions of the t − J model have been employed in numerical simulations, for instance, t − t ′ − J [23,24,25,26] or t − J − V [27,28,29],but the values given to the parameters are rather arbitrary, varying widely from one author to the other, the main objective being to exhibit qualitative collective effects. Among them the experimental evidence of the occurrence of stripes have focused attention in the recent past [30].…”
Section: Introductionmentioning
confidence: 99%